2016
DOI: 10.1016/j.numecd.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The innovative “Bio-Oil Spread” prevents metabolic disorders and mediates preconditioning-like cardioprotection in rats

Abstract: Background and aims: Obesity is often associated with an increased cardiovascular risk. The food industry and the associated research activities focus on formulating products that are a perfect mix between an adequate fat content and health. We evaluated whether a diet enriched with Bio-Oil Spread (SD), an olive oil-based innovative food, is cardioprotective in the presence of high-fat diet (HFD)-dependent obesity.Methods and Results: Rats were fed for 16 weeks with normolipidic diet (ND; fat: 6.2%), HFD (fat:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Collagen fibers were detected in parallel sections by staining with Picro Sirius Red (38). The sections were observed using a Zeiss Axioskop Microscope, and the images were digitalized by Axiocam 105 Color (Carl Zeiss, Oberkochen, Germany).…”
Section: Histologic Analysis and Apoptosis Detectionmentioning
confidence: 99%
“…Collagen fibers were detected in parallel sections by staining with Picro Sirius Red (38). The sections were observed using a Zeiss Axioskop Microscope, and the images were digitalized by Axiocam 105 Color (Carl Zeiss, Oberkochen, Germany).…”
Section: Histologic Analysis and Apoptosis Detectionmentioning
confidence: 99%
“…Taken together, polyphenol-rich food oils seem to represent a non-homogenous group with diverse effects on cardiovascular and cardiometabolic health that are mainly positive, but might be also neutral, and even negative (Table 1 , Ref. [ 16 , 17 , 18 , 21 , 22 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 43 , 45 , 47 , 48 , 49 , 52 , 55 , 56 , 59 , 65 , 66 , 69 , 70 , 71 , 72 , 73 , 77 , 78 , 80 , 81 , 82 , 83 , 84 , 89 , 90 , 91 , 93 , 94 , 95 , 110 , 111 , 112 , 113 , 114 , 120 , 121 , 122 , 123 , 124 , 148 , 159 , 160 , 162 , 166 , 167 , 169 , 179 , 189 , 201 , 203 , 206 , 209 , 210 , 211 ]). Some of the beneficial effects of these oils in cardiovascular system have been document...…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, extra virgin OO was able to decrease tumor necrosis factor- (TNF- ) level and oxidative stress in heart after MI [ 21 ]. Similarly, rats fed with a diet enriched with extra virgin OO (16 weeks) exhibited significantly improved systolic and diastolic post-ischemia/reperfusion (I/R) function and reduced the size of MI [ 22 ]. Moreover, a wide range of animal studies found oleuropein and hydroxytyrosol food supplementation to offer cardioprotection against MI in a model of acute MI and heart failure [ 23 , 24 , 25 , 26 ] or even in models of drug-induced cardiomyopathies [ 27 , 28 , 29 ].…”
Section: The Effect Of Olive Oil On Cardiovascular Health and Diseasesmentioning
confidence: 99%
“…Before killing, rats were anaesthetized with intraperitoneal injection of ethyl carbamate (2 g kg −1 body weight). Subsequently, the hearts were rapidly excised and immediately placed in ice‐cold perfusion Krebs‐Henseleit (KH) buffer, cannulated through the aorta with the use of a glass cannula and retrogradely perfused in the Langendorff apparatus at a constant flow rate of 12 mL min −1 (37°C), as previously described by Rocca et al 74 and Quintieri et al 75 Immediately after the cannulation, the apex of the left ventricle (LV) was pierced in order to avoid fluid accumulation and hearts were kept in a temperature‐controlled chamber (37°C). Perfusion was carried out by using a KH buffer (pH 7.4, gassed with 95% O 2 and 5% CO 2 ) containing in mmol L ‐1 :4.7 KCl, 113 NaCl, 25 NaHCO 3 , 1.8 CaCl 2 , 1.2 MgSO 4 , 1.2 KH 2 PO 4 , 1.1 mannitol, 11 glucose and 5 Na‐pyruvate.…”
Section: Methodsmentioning
confidence: 99%